2018
DOI: 10.1021/acs.iecr.7b04245
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclic Thiocarbonates from Thiiranes and CS2 with Silica-Immobilized Catalysts

Abstract: The synthesis of cyclic thiocarbonates by the cycloaddition of carbon disulfide (CS2) to thiiranes in the presence of silica-immobilized amine catalysts was investigated. The catalytic activities of the silica-immobilized catalysts toward the synthesis of cyclic thiocarbonates were higher than the activities of their homogeneous counterparts. The silica-supported catalysts strongly accelerated the cycloaddition of CS2 to thiiranes, and the pseudo-first-order rate constant of the silica-immobilized catalyst was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Because it is an abundant, inexpensive, and easy-to-handle liquid, the activation of CS 2 has attracted a great deal of attention in recent decades. The activation of CS 2 with transition metal complexes provided a variety of chemical transformations, including insertion, dimerization, disproportionation, and cycloaddition reactions, furnishing various sulfur-containing organic compounds. , Among these transformations, the cycloadditions with CS 2 are of particular interest because they allowed efficient construction of sulfur heterocycles . Furthermore, sulfur heterocycles exhibited many biological activities and pharmacological actions .…”
mentioning
confidence: 99%
“…Because it is an abundant, inexpensive, and easy-to-handle liquid, the activation of CS 2 has attracted a great deal of attention in recent decades. The activation of CS 2 with transition metal complexes provided a variety of chemical transformations, including insertion, dimerization, disproportionation, and cycloaddition reactions, furnishing various sulfur-containing organic compounds. , Among these transformations, the cycloadditions with CS 2 are of particular interest because they allowed efficient construction of sulfur heterocycles . Furthermore, sulfur heterocycles exhibited many biological activities and pharmacological actions .…”
mentioning
confidence: 99%
“…Choi and coworkers immobilized amine into a silica support in an attempt at recycling the catalyst but the cyclic trithiocarbonates were contaminated with linear polymers. 43 Here we demonstrate that using an appropriate initiator with a more electronegative anion than Cl − and higher temperatures, the coupling of CS 2 with PS essentially yields cyclic trithiocarbonates. The activation energy for the formation of cyclic trithiocarbonates is such that above 60 °C with F − as the anion, back-biting reactions largely predominate over propagation.…”
Section: Resultsmentioning
confidence: 65%
“…There is a need to use CS 2 as a sulfur feedstock in polymer synthesis for obtaining sulfur-rich polymers with high molecular weight. However, in the literature, many synthetic procedures have been reported for cyclic trithiocarbonates, which are used as a chain-transfer agent in living polymerization and only few papers can be found for the synthesis of poly­(trithiocarbonates). In 2007, Nozaki et al reported the first example of copolymerization of propylene sulfide (PS) with CS 2 in the presence of the well-known catalytic system, (salphen)­CrCl as the catalyst, where salphen is N , N ′-bis­(3,5-di- tert -butylsalicylidene)-1,2-diaminobenzene (see catalyst 1 in Chart ) and [PPN]Cl (bis­(triphenyl-phosphoranylidene)­ammonium chloride) is the cocatalyst .…”
Section: Introductionmentioning
confidence: 99%